Isolation and characterization of small antimicrobial peptides from Punica granatum against multi-drug resistant bacteria / Salha Khames Mohamed Ali Khames - Salha Khames , Mohamed Ali Khames (2019)
Pomegranate (Punica granatum) has long been used as a traditional medicinal plant, and its extracts are widely used for the treatment of diarrhoea and dysentery. Although P. granatum is known to possess potent antimicrobial compounds, its antimicrobial peptides (AMPs) have been poorly isolated and well characterized. In this study, peptides were isolated from pomegranate peel, leaf and stem, and their antibacterial activities against 11 different gram-negative enteropathogenic strains were screened using an agar well diffusion assay. The peptides were partially purified by 80% ammonium sulphate precipitation, and their antimicrobial activities were analysed. Gel filtration chromatography and semi-preparative high-performance liquid chromatography (HPLC) were performed to purify the peptides. The molecular weights of active peptides were identified by liquid chromatography-quadrupole time-of-flight mass spectrometry (Q-TOF LC/MS) analysis. Three potential antimicrobial peptides, two from the leaf fraction (LVF-AMP1 and LVF-AMP2) and one from the stem fraction (STF-AMP), with molecular weights of 386.17, 414.52 and 386.17 Da, respectively, were obtained. These active peptides inhibited the multidrug-resistant pathogenic strain Shigella flexneri serotype Y, with minimum inhibition concentration (MIC) values of 6.45, 7.55 and 6.05 μg ml-1, respectively. The results suggest that P. granatum is a source of plant antibacterial peptides, which may serve as potent and specific antimicrobial agents for the treatment of gastrointestinal diseases.